International Business Strategy of Indonesian Ethnic Fast Food: A PESTLE Analysis for Ayam Geprek Sa’i Expansion into the United Arab Emirates - Gertha Maria Gultom; Bintang Corvi Diphda; Theofani Trudy; Talitha Salsabila Putri G; Putri Alyaa Safira; Yoga Ramadhani; Husniyatul Hafidzah (LP2M IAIN Palopo, 2026)
This research aims to analyze the macro-environmental factors of the United Arab Emirates (UAE) using the PESTLE framework to evaluate the expansion feasibility of PT Ukhuwah Berkah Semesta’s brand, Ayam Geprek Sa'i. Employing a qualitative descriptive research design with a strategic case study approach, the study retrieves high-fidelity secondary data from credible international instruments, including the World Bank’s World Governance Indicators and the Corruption Perceptions Index. The findings reveal that the UAE offers a highly stable political environment with exceptional government effectiveness and low corruption. Economically, the UAE is a mostly free market with high purchasing power and a robust network of over 20 Comprehensive Economic Partnership Agreements (CEPAs), including with Indonesia. While the technological infrastructure is world-class, social and legal factors require meticulous alignment due to collectivist cultural values and mandatory Halal standardization policies. The results suggest that Indonesian SMEs should adopt a transnational strategy, balancing global operational standards with high local responsiveness to religious norms. Future studies should move beyond macro-environmental scanning to conduct empirical consumer perception research to further refine menu localization for the UAE's diverse expatriate population.